Occupational accidents in Slovak Military Forests and Estates: incidence, timing, and trends over 10 years - Allman, Michal; Dudáková, Zuzana; Jankovský, Martin (Frontiers in Public Health, 2024)
Forestry provides a wide range of employment opportunities worldwide and is seen as one of the high-risk industries in terms of occupational accidents. The submitted study analysed the injury rate in the Military Forests and Estates of the Slovak Republic (62.6 thousand ha) between 2013 and 2022. The data analyses included regression and correlation analyses, χ 2 tests to analyse the relationships between studied variables, and incidence rates. During the observed period, employees suffered 26 occupational accidents, of which 19.2 % were light, 57.7 % were registered, 23.1 % were severe, and 0 % were fatal. For every 1 million m 3 of harvested timber, 7.7 accidents occurred. The incidence rate during the observed period was 672.1/100,000 employees. The highest proportion of accidents was in the age group 51-60 years and in employees with the lowest length of work experience < 5 years. Regarding time, the highest proportion of occupational accidents occurred between 8:01 and 10:00 AM (53.8 %) and day-wise on Thursdays (46.2 %). The highest proportion of accidents occurred among forest workers (65.3 %) during pruning and silviculture activities (42.3 %). The most common injury site was forest stands (65.3 %). Superficial injuries (34.6 %) were the most common, mainly affecting the lower limbs (50 %). The most frequent material agents causing the accidents were work and transport areas as sources of worker fall (38.5 %), and the most frequent reason for an accident to occur was the lack of personal requirements for proper work performance (92.4 %), whereas only (3.8 %) of accidents occurred due to the use of forbidden or hazardous working procedures. The presented study identified the most vulnerable worker groups and provided an overview of the overall injury rate at the state forest company in Slovakia. The documentation can be incorporated into the safety strategies of forest enterprises.